Arabic Teacher Identity: In the Perspective of Performance during Distance Learning - Ilmiani, Aulia Mustika; Ritonga, Apri Wardana; Febrianta, Rita; Gadoum, Hamida (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
In the Covid-19 outbreak, the teacher should have the performance to be able to deal with the problems, opportunities, and challenges they face during distance learning. A phenomenological qualitative research method was used in this research to explore the identity of the Arabic language teacher at MIN 04 West Kotawaringin represented by their performance in the daily learning process. The data of this study were obtained from the analysis of interviews, observations and documentation. Interviews were conducted with two Arabic language teachers at MIN 04, students and the principal as the informants. The results showed that the teacher's performance could be seen from; the responsibilities in carrying out the task as a representation of their identity as an Arabic teacher who deal the problems and conditions about the learning facilities, enjoyable technique of teaching and learning, adapt to the use of digital-based media, take different learning resources, and take the initiative to use the most accessible and affordable methods. It was in line with the theory of teacher identity by Anne Graham and Renata Phelps that the teacher should be able to overcome the obstacles faced by both problems from students and infrastructure. This research could be a reference so that teachers can represent their performance, not only as a responsibility but also as a teacher's identity. Furthermore, this research hopefully can examine quantitatively regarding the identity of Arabic teacher in Central Kalimantan.